Mathematical modelling of the influence of electrostimulation in the osseointegration of dental implants (2013)
Electrostimulation denotes the influence of a static electric field (EF) on cell behavior and tissue formation. Several electrostimulation techniques have been reported to yield both increased rates of tissue recovery and reduced healing times in wounds. In dentistry, such techniques are being study and implemented to increase the bone formation around dental implants, which are devices inserted in the jaw bone to replace the root of a missing tooth. Although the biological effects of electrostimulation are well documented by experimental evidence, the exact underlying biological mechanisms influenced by the EF are still matter of discussion. In order to fill the gap, numerical models have gained interest as useful tools for providing information about the interaction paths. The purpose of this research is to analyze possible EF interaction mechanisms that may take place during bone formation around a dental implant using a numerical approach. Accordingly, we have formulated and implemented mathematical models describing the influence of the EF in the most critical biological processes leading to bone formation at the bone-dental implant interface. The numerical solutions reproduce the distribution of spatial-temporal patterns describing the influence of EF during blood clotting, cell migration, granulation tissue formation and formation of new bone. Since the numerical approach also allows us to analyze the influence of both chemical and electrical stimuli on cell dynamics, a numerical study of cell migration in the presence of an electric field, or electrotaxis, is also conducted. Numerical results indicate that electrostimulation promotes blood clot formation near the implant surface. Moreover, the presence of the electrical stimulus directs cell migration and increases the cell migration speed in agreement with the experimental findings on cell electrotaxis. A higher cell migration also accounts for a larger number of cells colonizing the implant surface. Furthermore, formation of granulation tissue in the presence of an EF is higher near the implant surface. Since the EF exposure increases both cell colonization and new tissue formation at the implant surface, numerical calculations show that the use of electrostimulation induces new bone formation at the bone-dental implant interface up to osseointegration (anchoring of the dental implant with the host bone) in less amount of time. These results are in agreement with experimental observations, and provide additional information on the EF interaction mechanisms with cells and tissues during wound healing, and ultimately, towards osseointegration. Given this agreement, the numerical framework is suitable to explore electrostimulation in other clinical scenarios, especially those dealing with different types of tissues and other electrostimulation modalities